Pembuatan Sistem Informasi Akuntansi dan Perhitungan PPN untuk CV. X - Limantara, Felicia; Purba, Kristo Radion; Setiabudi, Andy (Jurnal Infra, 2016)
At this time the CV. X does not have a structured accounting information system. Transactions are recorded manually, causing a slow information exchange and losses caused by error in the calculation of VAT. Based on the background of this problem, we designed a structured accounting informastion system along with the calculation of VAT. This application is made using Yii PHP Framework with PHP as programming language and MySQL for database. The results obtained from these aplication are purchases and sales recording, calculation of payable VAT for each month, purchases and sales report, VAT report, and financial report such as income statement, ownerâs equity, balance sheet and trial balance.